2020
DOI: 10.1371/journal.pone.0236122
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospital expenses and hospital stay among patients undergoing total laryngectomy: Cost effectiveness analysis

Abstract: Objective To determine the predictive factors of postoperative hospital stay and total hospital medical cost among patients who underwent total laryngectomy. Methods A total of 213 patients who underwent total laryngectomy in a tertiary referral center for tumor ablation were enrolled retrospectively between January 2009 and May 2018. Statistical analyses including Pearson's chi-squared test were used to determine whether there was a significant difference between each selected clinical factors and outcomes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Serum albumin concentration is commonly employed as a means of assessing malnutrition, which have been found to be prognostically significant in patients with head and neck cancer 14–18 . Our previous studies had also reported that increasing postoperative complication with poor prognosis were associated with lower serum albumin concentration in patients with head and neck cancer 19 …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Serum albumin concentration is commonly employed as a means of assessing malnutrition, which have been found to be prognostically significant in patients with head and neck cancer 14–18 . Our previous studies had also reported that increasing postoperative complication with poor prognosis were associated with lower serum albumin concentration in patients with head and neck cancer 19 …”
Section: Introductionmentioning
confidence: 96%
“…[14][15][16][17][18] Our previous studies had also reported that increasing postoperative complication with poor prognosis were associated with lower serum albumin concentration in patients with head and neck cancer. 19 To integrate the above biomarkers, Bernard et al introduced a new metric, the neutrophil-to-albumin ratio (NAR), which is calculated by dividing the absolute neutrophil count (ANC) by the serum albumin concentration. 20 NAR has been found to be an independent predictor of prognosis in patients with various cancers.…”
mentioning
confidence: 99%
“…Many often require respiratory support, such as ventilation. The length of stay for patients with a tracheostomy varies from 7 to 70 days (Median = 18) (Tsai et al., 2020). Standardised clinical practice guidelines on tracheostomy care for ventilated patients are available from the National Tracheostomy Safety Project (2012) and the Global Tracheostomy Collaborative (McCormick et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“… 5 For head and neck cancers, serum albumin and its associated biomarkers, such as prognostic nutrition index, and albumin-to-globulin ratio, have also been observed as predictors of survival and perioperative outcomes. 6 10 …”
Section: Introductionmentioning
confidence: 99%
“…5 For head and neck cancers, serum albumin and its associated biomarkers, such as prognostic nutrition index, and albumin-toglobulin ratio, have also been observed as predictors of survival and perioperative outcomes. [6][7][8][9][10] Alkaline phosphatase (ALP) is enriched in the kidney, bile duct, and liver and the elevation of ALP was also reported to be found in diverse malignancies and correlated to poor outcomes. 11,12 Albumin-to-alkaline phosphatase ratio (AAPR) was firstly investigated to be a novel prognosticator in hepatocellular carcinoma in 2015 and a series of studies have shown the clinical significance of prognosis in several malignancies.…”
Section: Introductionmentioning
confidence: 99%